ARTICULATE STORYLINE 3 SEBAGAI MEDIA PEMBELAJARAN IPA SEKOLAH PENGGERAK - Maysuri, Athanasia; Khotimah, Khusnul; Sukriadi, Sukriadi (Jurnal Visi Ilmu Pendidikan, 2024)
4C skills (Communication, Collaboration, Critical Thinking and Problem Solving, and Creativity and Innovation) are learned for the independent curriculum. The objectives of this study are; (1) the results of the feasibility of the educational media and (2) the responses of students and teachers to the developed educational media. The method used is the 3D-E development model or with 4 development procedures namely decide, design, develop and evaluate. The research subjects were 119 grade 5 students from 5 primary schools in Samarinda. The data collection technique used the evaluation questionnaire method, interviews and documentation. The results showed that: (1) The media was considered "feasible to try without revision" with a score of 3.8. (2) The results of media evaluation by the small group were 92.78% and included the category of "very good", the media evaluation by the large group obtained the results of 79.83% and included the category of "good", the results of media evaluation by the teacher obtained the final result of 99% and included the category of "very good" to be used in learning.